An architecture for e-learning infrastructures on a national level: a case study of the Afghanistan Research and Education Network. (2018) - Saay, Salim; Norta, Alex
National Research and Education Networks (NRENs) are for sharing resources among member organisations. NRENs play an important role in e-learning activities as they enable cross-organisational communication. Heterogeneous infrastructures used for e-learning are a challenge for system design, data integrity, and interoperability. This paper proposes an NREN e-learning reference architecture and affiliated NREN e-learning design patterns that consider communication, reliable access, a collaboration and interoperability between e-learning infrastructures. Research exists about different architectures including traditional e-learning systems, service-oriented cloud computing such as the service-oriented architecture (SOA) adaptations for education systems, e-learning systems and a service-oriented cloud computing architecture (SOCCA). However, no research has been carried out for NREN e-learning architectures. For deeper insight, we investigate in this paper an e-learning architecture based on the Afghanistan Research and Education Network (AfgREN). The reference e-learning architecture based on AfgREN provides guidance for the rapid development of different e-learning services and learning-analytical infrastructure for Afghanistan.